Spin scattering in ferromagnetic thin films - COEY, JOHN MICHAEL DAVID (American Physical Society, 1996)
By combining parallel and transverse magnetoresistance measurements on thin films of Co and Ni, the contribution of spin scattering at the domain walls is separated from the anisotropic magnetoresistance (AMR). A model, based on the Larmor-precession-induced deviation of the conduction electron spin direction during domain-wall traversal is developed. By using a scattering probability which varies with the cosine of the angle between the carrier spin and the local exchange field (as used for giant magnetoresistance systems) it is possible to account for the amplitude of the measured magnetoresistive effect.
PUBLISHED
Keywords: Physics